Phylogenomic analyses reveal reticulate evolution between Neomicrocalamus and Temochloa (Poaceae: Bambusoideae) - Cai, Zhuo-Yu; Niu, Zheng-Yang; Zhang, You-Yuan; Tong, Yi-Hua; Vu, Tien Chinh; Goh, Wei Lim; Sungkaew, Sarawood; Teerawatananon, Atchara; Xia, Nian-He (Frontiers in Plant Science, 2023)
Neomicrocalamus and Temochloa are closely related bamboo genera. However, when considered with newly discovered and morphologically similar material from China and Vietnam, the phylogenetic relationship among these three groups was ambiguous in the analyses based on DNA regions. Here, as a means of investigating the relationships among the three bamboo groups and exploring potential sources of genomic conflicts, we present a phylogenomic examination based on the whole plastome, single nucleotide polymorphism (SNP) and single-copy nuclear (SCN) gene datasets. Three different phylogenetic hypotheses were found. The inconsistency is attributed to the combination of incomplete lineage sorting and introgression. The origin of newly discovered bamboos is from introgressive hybridization between Temochloa liliana (which contributed 80.7% of the genome) and Neomicrocalamus prainii (19.3%) indicating the newly discovered bamboo is closer to Temochloa liliana in genetics. And the more similar morphology and closer distribution elevation also imply the comparatively closer relationship between Temochloa and newly discovered bamboos.